Spiritual Education of Tarekat Tuan Guru Haji Muhammad Mutawalli towards Wetu Telu Community - Sirajun Nasihin; Nuraenun Nuraenun; Surya Bayu Ansori; Mukhtar Mukhtar; Ahyar Rasydi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Tuan Guru Haji (TGH) Muhammad Mutawalli is one of the figures who have an important role in shaping and instilling spiritual education for wetu telu worshipers through the naqsyabandiyah wal-qadiriyah tarekat approach. The purpose of this research is to explore and find out TGH Muhammad Mutawalli's opinion on strengthening the spiritual education of the Wetu Telu congregation and the extent to which spiritual education is being strengthened. The method used is qualitative with a phenomenological approach, where this research seeks to uncover the hidden meaning behind the phenomenon of the Wetu Telu community in the Terara sub-district, East Lombok, West Nusa Tenggara. Data collection in this study was conducted using in-depth interviews, observation, and documentation of data found in the field. The results showed that the teachings of TGH Muhammad Mutawalli took the teachings of the Naqsyabandiyah Qadiriyah tarekat as a basis. This tarekat reflects the harmonization of various tarekat teachings, such as Naqsyabandiyah, Syaziliyah, Ghazaliyyah, and Syuhrawardiyyah. The spiritual education of the Sasak Wetu Telu community focuses on developing a love for Allah SWT, respect for nature, oral traditions, literary arts, and pepaosan as a store of spiritual messages. In conclusion, the teachings of TGH Muhammad Mutawalli in strengthening the spiritual education of the wetu telu congregation are indicated by the strength of the spirituality of the wetu telu congregation or the strengthening of belief in Allah SWT, the increasing intensity of worship of the wetu telu congregation, the establishment of houses of worship, and the creation of harmonization in the level of the social life of the community.